2016
DOI: 10.4238/gmr.15027350
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of microRNA-10b overexpression in breast cancer: a meta-analysis

Abstract: ABSTRACT. Many microRNAs (miRNAs) exhibit altered expression levels in cancers, and they may be considered as valuable prognostic biomarkers for cancers. Here we aimed to summarize the recent advances in miR10b involvement in human breast cancer and analyze the predicting role of miR-10b for survival. We searched, Embase, and Wanfang databases to identify studies on the prognostic role of miR-10b expression in breast cancer. A total of 770 patients from 7 eligible studies were included in the analysis. Pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This result is consistent with that of Liu et al, 64 who reported that miR-21 is a useful non-invasive biomarker to predict response to chemotherapy in HER2-positive breast cancer. Similarly, Wang et al 65 revealed that increased miR-10b expression might predict poor survival in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…This result is consistent with that of Liu et al, 64 who reported that miR-21 is a useful non-invasive biomarker to predict response to chemotherapy in HER2-positive breast cancer. Similarly, Wang et al 65 revealed that increased miR-10b expression might predict poor survival in patients with breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…TGFBR3 inhibits breast cancer progression through TGF-beta signaling (Lee et al, 2010). In addition, other molecules in module 1 such as ADAMTS5 (Fontanil et al, 2017), ARHGAP20 (Asaduzzaman et al, 2017), C2orf88 (Lo et al, 2015), EZH1 (Liu et al, 2012), FAM13A (Goto-Yamaguchi et al, 2018), FGF1 (Slattery et al, 2013), GNAL (Yi et al, 2009), GRAMD3 (Boiles et al, 2015), PELI2 (Zang et al, 2017), PLSCR4 (Sahay et al, 2015), PTPN14 (Belle et al, 2015), RBMS3 (Zhu et al, 2019a), SH3BGRL2 (Alexe et al, 2007;Wen et al, 2018), let-7c (Fu et al, 2017), mir-100 (Jiang et al, 2016b), mir-10b (Wang et al, 2016b), mir-125b (Wang et al, 2019a), mir-139 (Dai et al, 2017), and mir-21 (Yan et al, 2008;Yanwirasti and Arisanty, 2017;Zhu et al, 2019b) have been reported to play important roles in breast cancer. Module 2 had nine nodes, including two miRNAs, five lncRNAs, and two protein-coding genes.…”
Section: Modules In the Dysregulated Network Relate To The Survival Omentioning
confidence: 99%
“…Most of the studies included in this systematic review were performed on miR-10b (5 studies), on miR-21 (11 studies), on miR-34 family (8 studies) and on miR-200 family (10 studies). High level of miR-10b indicates poor prognosis in BC, correlating with angiogenesis and metastatic behaviors (increased tumor size, lymph node positivity and the high Ki-67 score) (139)(140)(141). Importantly, in NOD-SCID mice, the high miR-10b level led to distant metastasis, while in the 4T1 mouse mammary tumor metastasis model, the delivery of AntagomiR speci c for the silencing of miR-10b suppressed the distant metastasis (142,143).…”
Section: Discussionmentioning
confidence: 99%